Students’ Motivation in Reading English Recount Texts in Junior High School - Apoko, Tri Wintolo; Putri, Sintya Winanda; Inayah, Tarisa Marta; Maharani, Sekar Fuan (Universitas Muhammadiyah Tangerang, 2024)
Reading is one of the important skills in learning English and motivation plays an important role in influencing reading outcomes and experiences. Students' motivation needs to be increased as it affects other skills in learning English. This study aims to determine the level of the students’ motivation in reading English Recount Text. The descriptive quantitative research was carried out in this study in order to collect information or data. The instrument used for data collection was the Reading Motivation Questionnaire (RMQ) developed by Wigfield. Thirty students at one reputable junior high school were participated on filling in 15 statements regarding motivation in reading English Recount Text. The finding indicated that students’ motivation in reading English recount texts was at a high level. The most significant reason comes from extrinsic motivation in reading Recount Text. This study is helpful for teachers to discover factors affecting students' motivation in reading Recount Text.